A Fe 3+ Doped near-infrared luminescent material, preparation method and application thereof
Through Fe3+ doped near-infrared luminescent materials, the problems of narrow emission spectrum, poor thermal stability, high cost and toxic activation ions in the prior art are solved, and high efficiency, broadband near-infrared emission and good thermal stability are achieved. It is suitable for medical imaging, night vision, food analysis and other fields.
Patent Information
- Application Number
- CN202310519452.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-09
AI Technical Summary
Existing near-infrared luminescent materials have problems such as narrow emission spectrum range, poor thermal stability, high cost and toxic activation ions, which are difficult to meet the needs of broadband emission and security applications.
A near-infrared luminescent material doped with Fe3+, the general formula is A2M1-xSbO6:xFe3+, wherein element A is selected from Ca, Sr or Ba, element M is selected from Sc, Y, La, Gd, Lu, In, Al or Ga, 0
Under light source excitation in the wavelength range of 200-420nm, there is a strong emission intensity and a wide emission peak in the near infrared range, with an emission peak of about 750-1200nm. The material has high light conversion efficiency, wide absorption range, high thermal stability and good chemical stability, and the use of Fe3+ as the activated ions is non-toxic and harmless and low-cost.
Smart Images

Figure CN116554876B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of inorganic luminescent materials, and specifically relates to a Fe 3+ Doped near-infrared luminescent material, preparation method and application thereof. Background Art
[0002] Near-infrared light sources have the advantages of being fast, convenient, having low background noise, having a large penetration depth and non-invasive analysis, and are widely used in modern agriculture, safety monitoring, food processing, biomedicine, national defense and military industries, and other fields. Traditional near-infrared light sources include halogen tungsten lamps and semiconductor infrared LEDs. However, the former has the disadvantages of high power consumption, high bulb temperature, unstable spectrum, low efficiency and large size, while the latter only produces near-infrared emission with a narrow band, which cannot meet the application requirements of broadband emission. Therefore, it is limited in the design of small spectral analysis modules and many other practical applications. The new near-infrared fluorescence conversion light-emitting diode (pc-LED) has become a promising solid-state near-infrared light source due to its spectral adjustable, small size and high efficiency. The spectral performance (including spectral intensity and thermal stability) of pc-LED mainly depends on the spectral performance of near-infrared phosphor (i.e., near-infrared luminescent material). Therefore, the development of near-infrared (NIR) luminescent materials with high efficiency and broadband emission is of great practical significance.
[0003] Some studies have reported that rare earth ions are doped into inorganic matrices to prepare near-infrared luminescent materials. However, due to the ff transition of rare earth ions, most rare earth ions have relatively narrow excitation and emission spectra, which still cannot meet the application requirements of some infrared devices. At present, commonly used near-infrared luminescent materials are usually doped with trivalent chromium ions and use them as the luminescence center. They can usually provide a broadband emission spectrum in the range of 650 to 1200nm, but due to the toxicity, high price and poor thermal stability of chromium ions, they are limited in application. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a Fe 3+ Doped near-infrared luminescent material, preparation method and application thereof. The near-infrared luminescent material does not contain toxic substances, has good chemical stability, low cost, and has the characteristics of high luminescent efficiency and broadband emission.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In the first aspect, the present invention provides an Fe 3+ The doped near-infrared luminescent material has a general formula as shown in Formula I:
[0007] A2M 1-x SbO6:xFe 3+ Formula I;
[0008] Wherein, element A is selected from any one or more of Ca, Sr or Ba;
[0009] The element M is selected from any one or more of Sc, Y, La, Gd, Lu, In, Al or Ga;
[0010] 0<x≤0.05.
[0011] Preferably, 0.01<x≤0.05.
[0012] Preferably, the crystal structure of the near-infrared luminescent material is a double perovskite structure.
[0013] Preferably, 0.01<x≤0.05.
[0014] The chemical formula of the near-infrared luminescent material is selected from Sr2Sc 0.999 SbO6:0.1%Fe 3+ 、Ca2Sc 0.999 SbO6:0.1%Fe 3+ 、Sr2Sc 0.995 SbO6:0.5%Fe 3+ 、Ca2Sc 0.995 SbO6:0.5%Fe 3+ 、Sr2Sc 0.99 SbO6:1%Fe 3+ , Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ ,CaSrSc 0.99 SbO6:1%Fe 3+ 、CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3 + , Sr2Y 0.999 SbO6:0.1%Fe 3+ , Sr2Y 0.995 SbO6:0.5%Fe 3+ 、Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ ,Ba2Sc 0.99 SbO6:1%Fe 3+ ,Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ 、Sr2La 0.99SbO6:1%Fe 3+ 、Sr2Sc 0.89 La 0.1 SbO6:1%Fe 3+ 、Sr2Gd 0.99 SbO6:1%Fe 3+ , Sr 1.8 Ba 0.2 Sc 0.8 G 0.19 SbO6:1%Fe 3+ 、Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6:1%Fe 3+ 、 Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ 、Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ 、 Sr2Sc 0.89 Al 0.1 SbO6:1%Fe 3+ , Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe 3+ or Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6:1%Fe 3+ .
[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned near-infrared luminescent material, comprising the following steps:
[0016] By A2M 1-x SbO6:xFe 3+ A compound containing the A element, a compound containing the M element, a compound containing the Sb element and a compound containing the Fe element are mixed in a stoichiometric ratio to obtain a mixed material, which is then calcined to obtain a near-infrared luminescent material.
[0017] Preferably, the calcination treatment is carried out at a temperature of 1300 to 1600° C. and for a time of 1 to 2 hours.
[0018] Preferably, the heating rate of the calcination treatment is 1 to 10° C. / min.
[0019] Preferably, the compound containing element A is selected from any one or more of an oxide containing element A, a hydroxide containing element A, a halide containing element A or a carbonate containing element A.
[0020] Preferably, the compound containing the M element is selected from any one or more of an oxide containing the M element, a hydroxide containing the M element, a halide containing the M element, or an oxygen-containing acid salt containing the M element.
[0021] Preferably, the Sb-containing compound is selected from any one or more of Sb-containing oxides, Sb-containing halides or Sb-containing hydroxides.
[0022] Preferably, the Fe-containing compound is selected from any one or more of Fe-containing oxides, Fe-containing chlorides, Fe-containing hydroxides or Fe-containing carbonates.
[0023] In a third aspect, the present invention provides an application of the near-infrared luminescent material involved in the above technical solution in the fields of medical imaging, night vision, food analysis and solar cells.
[0024] In a fourth aspect, the present invention provides a near-infrared fluorescence conversion type light-emitting diode, comprising a chip and a phosphor encapsulating the near-infrared fluorescence conversion type light-emitting diode;
[0025] The phosphor is the near-infrared luminescent material involved in the above technical solution.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention provides a Fe 3+ Doped near-infrared luminescent material, wherein the near-infrared luminescent material is Fe 3+ As the activating ion, antimonate A2M 1-x SbO6 (0<x≤0.05) is used as the matrix material, wherein Fe 3+ By replacing the position of some elements M in the matrix material, Fe 3+ The ratio of Fe to M enables the material to emit strong emission intensity and wide emission peak in the near-infrared range under the excitation of a light source in the wavelength range of 200 to 420 nm, and the emission peak is about 750 to 1200 nm. In the present invention, the near-infrared luminescent material has high light conversion efficiency and wide absorption, high thermal stability, stable chemical properties, and uses Fe 3+ As an activated ion, it is non-toxic, harmless and cheap. It is an inorganic luminescent material with excellent performance and simple preparation method. It can be widely used in medical imaging, night vision, food analysis, solar cells and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Comparison of XRD patterns with the database standard card (ICSD-262994);
[0029] Figure 2 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ (i.e., SSSO-Fe 3+ ) and Sr2Sc 0.999 Comparison of diffuse reflectance spectra of SbO6 (i.e., SSSO);
[0030] Figure 3 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Excitation spectrum under 890nm light source monitoring;
[0031] Figure 4 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Spectral emission diagram under 334nm light source excitation;
[0032] Figure 5 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Quantum efficiency test result diagram;
[0033] Figure 6 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Variable temperature spectrum test result diagram;
[0034] Figure 7 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Spectral changes after soaking in water for a period of time;
[0035] Figure 8 The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Spectral changes after soaking in ethanol for a period of time;
[0036] Fig. 9 The near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe3+ Comparison of XRD patterns with the database standard card (ICSD-262995);
[0037] Fig.10 The near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ Excitation spectrum under 950nm light source monitoring;
[0038] Fig.11 The near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ Spectral emission diagram under 334nm light source excitation;
[0039] Fig.12 The near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ Quantum efficiency test result diagram;
[0040] Fig.13 The near-infrared luminescent material Sr2Y obtained in Example 9 0.999 SbO6:0.1%Fe 3+ Comparison of XRD patterns with the database standard card (ICSD-257789);
[0041] Fig.14 The near-infrared luminescent material Sr2Y obtained in Example 9 0.999 SbO6:0.1%Fe 3+ Excitation spectrum under 878nm light source monitoring;
[0042] Fig.15 The near-infrared luminescent material Sr2Y obtained in Example 9 0.999 SbO6:0.1%Fe 3+ Spectral emission diagram under 360nm light source excitation;
[0043] Fig.16 The near-infrared luminescent material Ba2Sc obtained in Example 13 0.89 Y 0.1 SbO6:1%Fe 3+ Comparison of XRD patterns with the database standard card (ICSD-33624);
[0044] Fig.17 The near-infrared luminescent material Ca obtained in Example 22 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe3+ Comparison of XRD patterns with the database standard card (ICSD-157007). DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Aiming at the problems of narrow emission spectrum range, poor thermal stability, high cost and toxic activated ions of near-infrared luminescent materials in the prior art, the present invention provides a Fe 3+ The doped near-infrared luminescent material has a general formula as shown in Formula I:
[0047] A2M 1-x SbO6:xFe 3+ Formula I.
[0048] Among them, element A is selected from any one or more of Ca, Sr or Ba; element M is selected from any one or more of Sc, Y, La, Gd, Lu, In, Al or Ga; 0<x≤0.05.
[0049] In some embodiments of the present invention, the value of x can be selected from 0.005, 0.01, 0.02, 0.03, 0.04 or 0.05, preferably 0.01<x≤0.05. The above point values are only listed and are not limited to them. Other point values within the numerical range are applicable and will not be repeated here.
[0050] In some embodiments of the present invention, the chemical formula of the near-infrared luminescent material can be selected from Sr2Sc 0.999 SbO6:0.1%Fe 3+ 、Ca2Sc 0.999 SbO6:0.1%Fe 3+ 、Sr2Sc 0.995 SbO6:0.5%Fe 3+ 、Ca2Sc 0.995 SbO6:0.5%Fe 3+ 、 Sr2Sc 0.99 SbO6:1%Fe 3+ , Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ ,CaSrSc0.99 SbO6: 1% Fe 3+ , CaSr 0.5 Ba 0.5 Sc 0.99 SbO6: 1% Fe 3+ , Sr2Y 0.999 SbO6: 0.1% Fe 3+ , Sr2Y 0.995 SbO6: 0.5% Fe 3+ , Sr2Sc 0.1 Y 0.89 SbO6: 1% Fe 3+ , Ba2Sc 0.99 SbO6: 1% Fe 3+ , Ba2Sc 0.89 Y 0.1 SbO6: 1% Fe 3+ , Sr2La 0.99 SbO6: 1% Fe 3+ , Sr2Sc 0.89 La 0.1 SbO6: 1% Fe 3+ , Sr2Gd 0.99 SbO6: 1% Fe 3+ , Sr 1.8 Ba 0.2 Sc 0.8 Gd 0.19 SbO6: 1% Fe 3+ , Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6: 1% Fe 3+ , Sr2Sc 0.89 Lu 0.1 SbO6: 1% Fe 3+ , Sr2Sc 0.89 Lu 0.1 SbO6: 1% Fe 3+ , Sr2Sc 0.89 Al 0.1 SbO6: 1% Fe 3+ , Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6: 1% Fe 3+ or Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6: 1% Fe 3+ .
[0051] In the present invention, the general formula of the near-infrared luminescent material is as shown in Formula I, including the activation ion Fe 3+ and by antimonate A2M 1-x The matrix material is composed of SbO6 (0<x≤0.05), wherein Fe 3+ By replacing the position of some elements M in the matrix material, the crystal structure of the matrix material is preferably a double perovskite structure. The present invention has found that the obtained doped Fe 3+ The near-infrared luminescent material still has a double perovskite structure. The double perovskite structure can provide a suitable site environment for trivalent iron ions, so that they can produce characteristic near-infrared emission. According to research, the near-infrared luminescent material can emit with strong emission intensity and wide emission peak in the near-infrared range under the excitation of a light source in the wavelength range of 200 to 420 nm, and the emission peak is about 750 to 1200 nm. In addition, the present invention uses non-toxic, harmless and inexpensive Fe 3+ As an activation ion, it solves the problems of high toxicity, high cost and poor thermal stability caused by using trivalent chromium ions as activation ions in the prior art.
[0052] The above-mentioned near-infrared luminescent material provided by the present invention can be prepared by a high-temperature solid-phase synthesis method or a sol-gel method well known to those skilled in the art. The present invention preferably adopts a high-temperature solid-phase synthesis method, which can be carried out according to technical means well known to those skilled in the art. In some embodiments of the present invention, it preferably includes the following steps:
[0053] By A2M 1-x SbO6:xFe 3+ A compound containing the A element, a compound containing the M element, a compound containing the Sb element and a compound containing the Fe element are mixed in a stoichiometric ratio to obtain a mixed material, which is then calcined to obtain a near-infrared luminescent material.
[0054] According to the present invention, first press A2M 1-x SbO6:xFe 3+The compound containing element A, the compound containing element M, the compound containing Sb and the compound containing Fe are mixed in a stoichiometric ratio to obtain a mixed material. Wherein, the compound containing element A (i.e., the compound containing Ca, Sr or Ba) is selected from any one or more of an oxide containing element A (i.e., an oxide containing Ca, Sr or Ba), a hydroxide containing element A (i.e., a hydroxide containing Ca, Sr or Ba), a halide containing element A (i.e., a halide containing Ca, Sr or Ba) or a carbonate containing element A (i.e., a carbonate containing Ca, Sr or Ba). Wherein, the compound containing Ca is preferably an oxide containing Ca or an oxyacid salt containing Ca, and the oxyacid salt containing Ca is preferably CaCO3; the compound containing Sr is preferably an oxide containing Sr or an oxyacid salt containing Sr, and the oxyacid salt containing Sr is preferably SrCO3; the compound containing Ba is preferably an oxide containing Ba or an oxyacid salt containing Ba, and the oxyacid salt containing Ba is preferably BaCO3.
[0055] The compound containing the M element (i.e., a compound containing Sc, Y, La, Gd, Lu, In, Al or Ga) is selected from any one or more of an oxide containing the M element (i.e., an oxide containing Sc, Y, La, Gd, Lu, In, Al or Ga), a hydroxide containing the M element (i.e., a hydroxide containing Sc, Y, La, Gd, Lu, In, Al or Ga), a halide containing the M element (i.e., a halide containing Sc, Y, La, Gd, Lu, In, Al or Ga) or an oxygen-containing acid salt containing the M element (i.e., an oxygen-containing acid salt containing Sc, Y, La, Gd, Lu, In, Al or Ga). Among them, the Sc-containing compound is preferably an oxide containing Sc or an oxyacid salt containing Sc, the Sc-containing oxide is preferably Sc2O3, and the Sc-containing oxyacid salt is preferably Sc2(CO3)3; the Y-containing compound is preferably an oxide containing Y or an oxyacid salt containing Y, the Y-containing oxide is preferably Y2O3, and the Y-containing oxyacid salt is preferably Y2(CO3)3; the La-containing compound is preferably an oxide containing La or an oxyacid salt containing La, the La-containing oxide is preferably La2O3, and the La-containing oxyacid salt is preferably La2(CO3)3; the Gd-containing compound is preferably an oxide containing Gd or an oxyacid salt containing Gd, the Gd-containing oxide is preferably Gd2O3, and the Gd-containing oxyacid salt is preferably Gd2(CO3)3; the Lu-containing The compound is preferably an oxide containing Lu or an oxyacid salt containing Lu, the oxide containing Lu is preferably Lu2O3, and the oxyacid salt containing Lu is preferably Lu2(CO3)3 or Lu(OH)3; the compound containing Al is preferably an oxide containing Al or an oxyacid salt containing Al, the oxide containing Al is preferably Al2O3, and the oxyacid salt containing Al is preferably Al(NO3)3; the compound containing In is preferably an oxide containing In or an oxyacid salt containing In, the oxide containing In is preferably In2O3, and the oxyacid salt containing In is preferably In(NO3)3; the compound containing Ga is preferably an oxide containing Ga or an oxyacid salt containing Ga, the oxide containing Ga is preferably Ga2O3, and the oxyacid salt containing Ga is preferably Ga(NO3)3.
[0056] The Sb-containing compound is selected from any one or more of a Sb-containing oxide, a Sb-containing halide or a Sb-containing hydroxide, preferably a Sb-containing oxide, and the Sb-containing oxide is preferably Sb2O3.
[0057] The Fe-containing compound is selected from any one or more of Fe-containing oxides, Fe-containing chlorides, Fe-containing hydroxides or Fe-containing carbonates. Among them, the Fe-containing oxide is preferably Fe2O3, the Fe-containing carbonate is preferably Fe2(CO3)3, the Fe-containing chloride is preferably FeCl3, and the Fe-containing hydroxide is preferably Fe(OH)3.
[0058] In some embodiments of the present invention, after obtaining the mixed material, it is preferred to first grind the mixed material to ensure uniform mixing, and then perform calcination. The grinding is preferably performed in an agate mortar.
[0059] According to the present invention, the mixed material in the above technical solution is calcined to obtain the near-infrared luminescent material. In some embodiments of the present invention, the calcination treatment is preferably carried out in an air atmosphere, and the temperature is increased to 1300-1600°C, preferably 1400-1500°C, at a heating rate of 1-10°C / min, preferably 2-8°C / min, and more preferably 4-5°C / min, and calcined for 1-2h, preferably 1.5-1.8h. The present invention preferably places the mixed material in a quartz crucible and calcines it in a muffle furnace.
[0060] In some embodiments of the present invention, after calcination, the sample is preferably naturally cooled to room temperature and then ground to ensure that its average particle size is 0.01-20 μm, preferably 0.1-15 μm, more preferably 5-10 μm, so as to facilitate its subsequent use as a phosphor for encapsulating LEDs. The present invention has no particular restrictions on the grinding method, and conventional methods can be used, such as manual grinding with a mortar or grinding in a ball grinder. The product after uniform grinding can be sealed or stored under nitrogen atmosphere protection. The room temperature refers to a temperature of 20-30°C, preferably 25°C.
[0061] The high-temperature solid-phase synthesis method provided by the present invention is used to prepare near-infrared luminescent materials. The raw materials used and the final products do not contain toxic or harmful substances. The raw materials are cheap, the synthesis method is simple and efficient, and is suitable for industrial production.
[0062] It should be noted that the near-infrared luminescent material provided by the present invention includes, in addition to the inorganic compound represented by the general formula I, a mixture of other crystalline phases or amorphous phases (including element A, element M, Sb and Fe), and the mixture of other crystalline or amorphous phases is an inorganic luminescent material different from the inorganic compound represented by the general formula I. In the near-infrared luminescent material provided by the present invention, the mass fraction of the inorganic compound represented by the general formula I is preferably not less than 20%.
[0063] The near-infrared luminescent material involved in the above technical solution of the present invention can be applied to many fields such as medical imaging, night vision, food analysis and solar cells.
[0064] After research, the near-infrared luminescent material provided by the present invention can emit with strong emission intensity and wide emission peak in the near-infrared range under the excitation of a light source in the wavelength range of 200 to 420 nm, and the emission peak is about 750 to 1200 nm. For example, the near-infrared luminescent material Sr2Sc 0.999 SbO6:0.1%Fe3+ The main peak of the excitation spectrum under 890nm light source monitoring is around 334nm, and the main peak of the spectrum emission under 334nm light source excitation is near 890nm. The calculated half-height width is 116nm, indicating that it has a wide emission in the near-infrared spectrum. 0.999 SbO6:0.1%Fe 3+ They have similar spectral properties and will not be described in detail here.
[0065] The infrared luminescent material is very suitable for preparing a near-infrared fluorescence conversion light-emitting diode (pc-LED) because it has strong emission intensity and wide emission peak in the near-infrared range. Based on this, the present invention also provides a near-infrared fluorescence conversion light-emitting diode, including a chip and a phosphor encapsulating the near-infrared fluorescence conversion light-emitting diode, wherein the phosphor is the near-infrared luminescent material involved in the above technical solution.
[0066] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention can be purchased from the market or prepared according to conventional preparation methods well known to those skilled in the art. Wherein, the "AR" involved in the following examples represents analytical grade.
[0067] Example 1
[0068] This embodiment provides a near-infrared luminescent material Sr2Sc 0.999 SbO6:0.1%Fe 3+ , and its preparation method is as follows:
[0069] According to Sr2Sc 0.999 SbO6:0.1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. Then the obtained sample powder was placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5℃ / min to 1500℃ for 6h to obtain the near-infrared luminescent material Sr2Sc 0.999 SbO6:0.1%Fe 3+ .
[0070] The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ The XRD spectrum comparison with the database standard card (ICSD-262994) is shown in the figure below. Figure 1As shown, it can be seen that the obtained near-infrared luminescent material has no obvious impurities, and its XRD spectrum is consistent with the spectrum of the standard data, proving that the near-infrared luminescent material is a double perovskite structure. 0.999 SbO6:0.1%Fe 3+ (i.e., SSSO-Fe 3+ ) and Sr2Sc 0.999 The diffuse reflectance spectrum comparison of SbO6 (ie, SSSO) is shown in Figure 2 As shown, it can be seen that compared with SSSO, SSSO-Fe 3+ There is a relatively strong absorption peak in the range of 300-400nm, indicating that SSSO-Fe 3+ It has a wide absorption in the ultraviolet range. The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ The excitation spectrum under 890nm light source monitoring is as follows Figure 3 As shown, it can be seen that the main peak is around 334nm. The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ The spectral emission diagram under 334nm light source excitation is as follows Figure 4 As shown, it can be seen that its main peak is around 890nm, and the calculated half-height width is 116nm, indicating that it has a wide emission in the near-infrared spectrum. 0.999 SbO6:0.1%Fe 3+ The quantum efficiency (the quantum efficiency is the external quantum efficiency) was tested in an FL1000 spectrometer with an integrating sphere.
[0071] Test results such as Figure 5 As shown, it can be seen that with 334nm as the excitation light source, the obtained emission peak is very high, and the test data result is 54.2%, indicating that it has high quantum efficiency and thus good photoelectric conversion efficiency.
[0072] The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ Conduct variable temperature spectrum test, the test method is as follows:
[0073] Near infrared luminescent material Sr2Sc 0.999 SbO6:0.1%Fe 3+ Place it in a spectrometer with a temperature control system, control the temperature change, and observe the change in its spectral intensity at different temperatures.
[0074] Test results such as Figure 6As shown, it can be seen that it has good thermal stability.
[0075] The near-infrared luminescent material Sr2Sc obtained in Example 1 0.999 SbO6:0.1%Fe 3+ The spectrum test was carried out in water and anhydrous ethanol respectively. The test method is as follows:
[0076] Near infrared luminescent material Sr2Sc 0.999 SbO6:0.1%Fe 3+ Immerse it in water or ethanol, test the spectrum at regular intervals, and observe the changes in the spectrum.
[0077] Test results such as Figure 7 and Figure 8 As shown, Figure 7 Sr2Sc 0.999 SbO6:0.1%Fe 3+ Spectral changes after soaking in water for a period of time, Figure 8 Sr2Sc 0.999 SbO6:0.1%Fe 3+ The spectral changes after soaking in alcohol for a period of time are shown in the figure. Figure 7 and Figure 8 It can be seen that after soaking in water or anhydrous ethanol for a period of time, Sr2Sc 0.999 SbO6:0.1%Fe 3+ The spectrum of Sr2Sc 0.999 SbO6:0.1%Fe 3+ It has good chemical stability in water or anhydrous ethanol.
[0078] Example 2
[0079] This embodiment provides a near-infrared luminescent material Ca2Sc 0.999 SbO6:0.1%Fe 3+ , and its preparation method is as follows:
[0080] According to Ca2Sc 0.999 SbO6:0.1%Fe 3+ According to the stoichiometric ratio, CaCO3(AR), Sc2O3(AR), Al2O3(AR), and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ca2Sc 0.999 SbO6:0.1%Fe 3+ .
[0081] Near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ The XRD spectrum comparison with the database standard card (ICSD-262995) is shown in the figure below. Fig. 9 As shown, it can be seen that the obtained near-infrared luminescent material has no obvious impurities, and its XRD spectrum is consistent with the spectrum of the standard data, proving that the near-infrared luminescent material is a double perovskite structure. 0.999 SbO6:0.1%Fe 3+ The excitation spectrum under 950nm light source monitoring is as follows Fig.10 As shown, it can be seen that the main peak is around 334nm. The near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ The spectral emission diagram under 334nm light source excitation is as follows Fig.11 As shown, it can be seen that its main peak is near 950nm, and the calculated half-width is 126nm, indicating that it has a wide emission in the near-infrared spectrum.
[0082] Referring to the quantum efficiency test method in Example 1, the near-infrared luminescent material Ca2Sc obtained in Example 2 0.999 SbO6:0.1%Fe 3+ Tested, the results are as follows Fig.12 As shown, it can be seen that under the excitation of 334nm light source, the emission peak is very high, and the external quantum efficiency test result is 45%, indicating that it has high quantum efficiency and thus good photoelectric conversion efficiency.
[0083] Example 3
[0084] This embodiment provides a near-infrared luminescent material Sr2Sc 0.995 SbO6:0.5%Fe 3+ , and its preparation method is as follows:
[0085] According to Sr2Sc 0.995 SbO6:0.5%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at 3℃ / min to 1400℃ for 8h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.995 SbO6:0.5%Fe 3+ .
[0086] The near-infrared luminescent material Sr2Sc 0.995 SbO6:0.5%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 1.
[0087] Example 4
[0088] This embodiment provides a near-infrared luminescent material Ca2Sc 0.995 SbO6:0.5%Fe 3+ , and its preparation method is as follows:
[0089] According to Ca2Sc 0.995 SbO6:0.5%Fe 3+ According to the stoichiometric ratio, CaCO3(AR), Sc2O3(AR), Al2O3(AR), and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ca2Sc 0.995 SbO6:0.5%Fe 3+ .
[0090] The near-infrared luminescent material Ca2Sc 0.999 SbO6:0.5%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 2.
[0091] Example 5
[0092] This embodiment provides a near-infrared luminescent material Sr2Sc 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0093] According to Sr2Sc 0.99 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.99 SbO6:1%Fe 3+ .
[0094] The near-infrared luminescent material Ca2Sc 0.999SbO6:0.5%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectrum of Example 1.
[0095] Example 6
[0096] This embodiment provides a near-infrared luminescent material Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0097] According to Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ According to the stoichiometric ratio, CaCO3(AR), SrCO3(AR), BaCO3(AR), Sc2O3(AR), Y2O3(AR), and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3 + .
[0098] The near-infrared luminescent material Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 2.
[0099] Example 7
[0100] This embodiment provides a near-infrared luminescent material CaSrSc 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0101] According to CaSrSc 0.99 SbO6:1%Fe 3+According to the stoichiometric ratio, CaCO3(AR), SrCO3(AR), Sc2O3(AR), Sb2O3(AR), Al2O3(AR), and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material CaSrSc 0.99 SbO6:1%Fe 3+ .
[0102] The near-infrared luminescent material Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 2.
[0103] Example 8
[0104] This embodiment provides a near-infrared luminescent material CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0105] According to CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3+ According to the stoichiometric ratio, CaCO3(AR), SrCO3(AR), BaCO3(AR), Sc2O3(AR), Sb2O3(AR), and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3+ .
[0106] The near-infrared luminescent material CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 2.
[0107] Example 9
[0108] This embodiment provides a near-infrared luminescent material Sr2Y 0.999 SbO6:0.1%Fe 3+ , and its preparation method is as follows:
[0109] According to Sr2Y 0.999 SbO6:0.1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Y2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5℃ / min to 1500℃ for 6h to obtain the inorganic near-infrared luminescent material Sr2Y 0.999 SbO6:0.1%Fe 3+ .
[0110] Near-infrared luminescent material Sr2Y obtained in Example 9 0.999 SbO6:0.1%Fe 3+ The XRD spectrum comparison with the database standard card (ICSD-257789) is shown in the figure below. Fig.13 As shown, it can be seen that the obtained near-infrared luminescent material has no obvious impurities, and its XRD spectrum is consistent with the spectrum of the standard data, proving that the near-infrared luminescent material is a double perovskite structure. 0.999 SbO6:0.1%Fe 3+ The excitation spectrum under 878nm light source monitoring is as follows Fig.14 As shown, it can be seen that the main peak is around 360nm. 0.999 SbO6:0.1%Fe 3+ The spectral emission diagram under 360nm light source excitation is as follows Fig.15 As shown, it can be seen that its main peak is near 878nm, and the calculated half-width is 113nm, indicating that it has wide emission in the near-infrared spectral range.
[0111] Example 10
[0112] This embodiment provides a near-infrared luminescent material Sr2Y 0.995 SbO6:0.5%Fe 3+ , and its preparation method is as follows:
[0113] According to Sr2Y 0.995 SbO6:0.5%Fe 3+According to the stoichiometric ratio, Sr2CO3(AR), Y2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at 4°C / min to 1400°C for 8h to obtain the inorganic near-infrared luminescent material Sr2Y 0.995 SbO6:0.5%Fe 3+ .
[0114] The near-infrared luminescent material Sr2Y 0.995 SbO6:0.5%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectrum of Example 9.
[0115] Embodiment 11
[0116] This embodiment provides a near-infrared luminescent material Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0117] According to Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Y2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1600°C for 5h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ .
[0118] The near-infrared luminescent material Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectrum of Example 9.
[0119] Example 12
[0120] This embodiment provides a near-infrared luminescent material Ba2Sc 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0121] Follow Ba2Sc 0.99SbO6:1%Fe 3+ Ba2CO3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed in a stoichiometric ratio, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ba2Sc 0.99 SbO6:1%Fe 3+ .
[0122] Embodiment 13
[0123] This embodiment provides a near-infrared luminescent material Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0124] Follow Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Ba2CO3(AR), Sc2O3(AR), Y2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ .
[0125] Example 13: Near-infrared luminescent material Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ The XRD spectrum comparison with the database standard card (ICSD-33624) is shown in the figure below. Fig.16 As shown, it can be seen that the obtained near-infrared luminescent material has no obvious impurities, and its XRD spectrum is consistent with the spectrum of the standard data, proving that the near-infrared luminescent material is a double perovskite structure.
[0126] Embodiment 14
[0127] This embodiment provides a near-infrared luminescent material Sr2La 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0128] According to Sr2La 0.99 SbO6:1%Fe 3+According to the stoichiometric ratio, Sr2CO3(AR), La2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at 5℃ / min to 1500℃ for 6h to obtain the inorganic near-infrared luminescent material Sr2La 0.99 SbO6:1%Fe 3+ .
[0129] Embodiment 15
[0130] This embodiment provides a near-infrared luminescent material Sr2Sc 0.89 La 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0131] According to Sr2Sc 0.89 La 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), La2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.89 La 0.1 SbO6:1%Fe 3+ .
[0132] Example 16
[0133] This embodiment provides a near-infrared luminescent material Sr2Gd 0.99 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0134] According to Sr2Gd 0.99 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Gd2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Sr2Gd 0.99 SbO6:1%Fe 3+ .
[0135] Embodiment 17
[0136] This embodiment provides a near-infrared luminescent material Sr 1.8 Ba 0.2 Sc 0.8 G 0.19 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0137] According to Sr 1.8 Ba 0.2 Sc 0.8 G 0.19 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Ba2CO3(AR), Gd2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Sr 1.8 Ba 0.2 Sc 0.8 G 0.19 SbO6:1%Fe 3+ .
[0138] Embodiment 18
[0139] This embodiment provides a near-infrared luminescent material Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0140] According to Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Lu2O3(AR), Sc2O3(AR), Y2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at 5℃ / min to 1500℃ for 6h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6:1%Fe 3+ .
[0141] Embodiment 19
[0142] This embodiment provides a near-infrared luminescent material Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0143] According to Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Lu2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5℃ / min to 1500℃ for 6h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ .
[0144] Embodiment 20
[0145] This embodiment provides a near-infrared luminescent material Sr2Sc 0.89 Lu 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0146] According to Sr 1.8 Ba 0.2 Sc 0.79 Y 0.1 Lu 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Ba2CO3(AR), Lu2O3(AR), Sc2O3(AR), Y2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1600°C for 5h to obtain the inorganic near-infrared luminescent material Sr 1.8 Ba 0.2 Sc 0.79 Y 0.1 Lu 0.1 SbO6:1%Fe 3+ .
[0147] Embodiment 21
[0148] This embodiment provides a near-infrared luminescent material Sr2Sc 0.89 Al 0.1SbO6:1%Fe 3+ , and its preparation method is as follows:
[0149] According to Sr2Sc 0.89 Al 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Sr2CO3(AR), Al2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed respectively, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5℃ / min to 1500℃ for 6h to obtain the inorganic near-infrared luminescent material Sr2Sc 0.89 Al 0.1 SbO6:1%Fe 3+ .
[0150] The near-infrared luminescent material Sr2Sc 0.89 Al 0.1 SbO6:1%Fe 3+ The obtained XRD spectrum and the obtained spectral emission spectrum and excitation spectrum are similar to the corresponding spectra obtained in Example 1.
[0151] Embodiment 22
[0152] This embodiment provides a near-infrared luminescent material Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0153] According to Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Ca2CO3(AR), Sr2CO3(AR), Al2O3(AR), Sc2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe 3+ .
[0154] Example 22 The near-infrared luminescent material Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6:1%Fe 3+11 The XRD spectrum comparison with the database standard card (ICSD-157007) is shown in the figure below. Fig.17 As shown, it can be seen that the obtained near-infrared luminescent material has no obvious impurities, and its XRD spectrum is consistent with the spectrum of the standard data, proving that the near-infrared luminescent material is a double perovskite structure.
[0155] The fluorescence spectrum properties of the inorganic near-infrared emitting luminescent material obtained in this process are similar to those in Example 1.
[0156] Embodiment 23
[0157] This embodiment provides a near-infrared luminescent material Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6:1%Fe 3+ , and its preparation method is as follows:
[0158] According to Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6:1%Fe 3+ According to the stoichiometric ratio, Ca2CO3(AR), Sr2CO3(AR), Ga2O3(AR), Sc2O3(AR), Al2O3(AR), Sb2O3(AR) and Fe2O3(AR) were weighed and mixed, and then the weighed raw materials were placed in an agate mortar and ground until the mixture was uniform. The obtained sample powder was then placed in a quartz crucible and sintered in a muffle furnace at a temperature of 5°C / min to 1500°C for 6h to obtain the inorganic near-infrared luminescent material Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6:1%Fe 3+ .
[0159] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A kind of Fe 3+ The doped near-infrared luminescent material is characterized in that The chemical formula of the near-infrared luminescent material is selected from Sr2Sc 0.999 SbO6:0.1%Fe 3+ 、Ca2Sc 0.999 SbO6:0.1%Fe 3+ 、Sr2Sc 0.995 SbO6:0.5%Fe 3+ 、Ca2Sc 0.995 SbO6:0.5%Fe 3+ 、Sr2Sc 0.99 SbO6:1%Fe 3+ , Ca 1.8 Sr 0.1 Ba 0.1 Y 0.1 Sc 0.89 SbO6:1%Fe 3+ ,CaSrSc 0.99 SbO6:1%Fe 3+ 、CaSr 0.5 Ba 0.5 Sc 0.99 SbO6:1%Fe 3+ , Sr2Y 0.999 SbO6:0.1%Fe 3+ , Sr2Y 0.995 SbO6:0.5%Fe 3+ 、Sr2Sc 0.1 Y 0.89 SbO6:1%Fe 3+ ,Ba2Sc 0.99 SbO6:1%Fe 3+ ,Ba2Sc 0.89 Y 0.1 SbO6:1%Fe 3+ 、Sr2La 0.99 SbO6:1%Fe 3+ 、Sr2Sc 0.89 La 0.1 SbO6:1%Fe 3+ 、Sr2Gd 0.99 SbO6:1%Fe 3+ , Sr 1.8 Ba 0.2 Sc 0.8 G 0.19 SbO6:1%Fe 3+ 、Sr2Sc 0.5 Y 0.39 Lu 0.1 SbO6:1%Fe 3+ 、Sr2Sc 0.89 Lu 0.1 SbO6: 1% Fe 3+ , Sr2Sc 0.89 Lu 0.1 SbO6: 1% Fe 3+ , Sr2Sc 0.89 Al 0.1 SbO6: 1% Fe 3+ , Ca 0.5 Sr 1.5 Sc 0.89 Al 0.1 SbO6: 1% Fe 3+ or Ca 0.5 Sr 1.5 Sc 0.79 Ga 0.1 Al 0.1 SbO6: 1% Fe 3+ .
2. The near-infrared luminescent material according to claim 1, characterized in that: The crystal structure of the near-infrared luminescent material is a double perovskite structure.
3. The method for preparing the near-infrared luminescent material according to claim 1 or 2, characterized in that: The following steps are involved: A compound containing the element A, a compound containing the element M, a compound containing Sb and a compound containing Fe are mixed to obtain a mixed material, and then the mixed material is calcined to obtain a near-infrared luminescent material; Element A is selected from any one or more of Ca, Sr or Ba; The M element is selected from any one or more of Sc, Y, La, Gd, Lu, Al or Ga.
4. The preparation method according to claim 3, characterized in that: The calcination treatment is carried out at a temperature of 1300-1600° C. and for a time of 1-2 h.
5. The preparation method according to claim 3, characterized in that: The heating rate of the calcination treatment is 1-10 °C / min.
6. The preparation method according to claim 3, characterized in that: The compound containing element A is selected from any one or more of an oxide containing element A, a hydroxide containing element A, a halide containing element A or a carbonate containing element A; The compound containing the element M is selected from any one or more of an oxide containing the element M, a hydroxide containing the element M, a halide containing the element M, or an oxygen-containing acid salt containing the element M; The Sb-containing compound is selected from any one or more of Sb-containing oxides, Sb-containing halides or Sb-containing hydroxides; The Fe-containing compound is selected from any one or more of Fe-containing oxides, Fe-containing chlorides, Fe-containing hydroxides or Fe-containing carbonates.
7. Application of the near-infrared luminescent material according to claim 1 or 2 or the near-infrared luminescent material prepared by the preparation method according to any one of claims 3 to 6 in the fields of medical imaging, night vision, food analysis and solar cells.
8. A near-infrared fluorescence conversion light-emitting diode, characterized in that: It comprises a chip and phosphor encapsulating the near-infrared fluorescence conversion type light-emitting diode; The phosphor is the near-infrared luminescent material according to claim 1 or 2 or the near-infrared luminescent material prepared by the preparation method according to any one of claims 3 to 6.
Citation Information
Patent Citations
High-performance oxide near-infrared luminescent material as well as preparation method and application thereof
CN115322773A